Pragmatic and Discursive Features of Ecological Speech Units in English and Uzbek Literary Texts - Safarova, Dildora Mamatovna (The Lingua Spectrum, 2026)
This article conducts a comparative analysis of the pragmatic and discursive features of ecological speech units in English and Uzbek literary texts. The aim of the study is to reveal the expression of attitudes toward the environment through speech units (metaphors, speech acts, discursive strategies). Based on ecolinguistics theory (Stibbe, 2015) and pragmato-discursive approaches, a corpus of texts was analyzed: English (e.g., Cormac McCarthy’s “The Road” and novels influenced by Rachel Carson) and Uzbek (“Shaytanat”, “Zilzila” by Tohir Malik; modern ecological stories). Methods: qualitative discourse analysis, classification of pragmatic speech acts, and identification of discursive strategies. The results show that English texts are dominated by anthropocentric metaphors (nature as “enemy”), while Uzbek texts emphasize harmony and responsibility (nature as “mother” or “friend”). Pragmatically, warning and appeal speech acts are present in both languages, but discursively English texts highlight individualism, Uzbek texts – collective responsibility. The study emphasizes the role of language in shaping ecological awareness and provides practical recommendations for literary translation and ecolinguistics. The findings open up possibilities for using language to promote social change in times of ecological crisis.